2016
DOI: 10.1016/j.celrep.2016.08.064
|View full text |Cite
|
Sign up to set email alerts
|

Bcl11a Deficiency Leads to Hematopoietic Stem Cell Defects with an Aging-like Phenotype

Abstract: SUMMARY B cell CLL/lymphoma 11A (BCL11A) is a transcription factor and regulator of hemoglobin switching that has emerged as a promising therapeutic target for sickle cell disease and thalassemia. In the hematopoietic system, BCL11A is required for B lymphopoiesis, yet its role in other hematopoietic cells, especially hematopoietic stem cells (HSCs) remains elusive. The extensive expression of BCL11A in hematopoiesis implicates context-dependent roles, highlighting the importance of fully characterizing its fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 44 publications
6
67
0
Order By: Relevance
“…However, a sharp decline in indel frequency post-transplant was observed in the coding ZFN-treated group, but much less so in the enhancer ZFN-treated group (Figure 5B), despite that the CD34 + cell viabilities were comparable after electroporation at the time of harvesting (Table S1). This is consistent with the recently described role of BCL11A in maintaining HSC functions 22, 35, 36. Taken together, the negative impact of exon 2 disruption of the BCL11A gene on both terminal erythroid enucleation as well as on HSC function strongly argues against disruption of the coding sequence of BCL11A as a therapeutic strategy.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, a sharp decline in indel frequency post-transplant was observed in the coding ZFN-treated group, but much less so in the enhancer ZFN-treated group (Figure 5B), despite that the CD34 + cell viabilities were comparable after electroporation at the time of harvesting (Table S1). This is consistent with the recently described role of BCL11A in maintaining HSC functions 22, 35, 36. Taken together, the negative impact of exon 2 disruption of the BCL11A gene on both terminal erythroid enucleation as well as on HSC function strongly argues against disruption of the coding sequence of BCL11A as a therapeutic strategy.…”
Section: Resultssupporting
confidence: 90%
“…Although Bjurstrom and colleagues 46 show that BCL11A exon 2-edited mobilized PB-CD34 + can successfully engraft NSG mice, we found the engraftment by edited BM-CD34 + cells to be severely impaired (Figure 6). Because it has recently been reported that BCL11A not only is important for lymphoid development, 49 but also plays a critical role in maintaining vital HSC functions,22, 35, 36 a defect in the engraftment of exon 2 KO/KO cells was therefore not unexpected. In contrast to being essential for preserving HSC functions, it has been reported that BCL11A is dispensable for RBC production based on data obtained from erythroid-specific knockout of BCL11A in mice and shRNA knockdown of BCL11A in primary human erythroblasts 22, 30.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has shown efficiency in all previous studies, and it is favored for several reasons. BCL11A inactivation through NHEJ repair is more efficient than the homology-mediated repair needed to recreate known HPFH sites in the γ-globin promoter, and inactivation of the erythroid-specific BCL11a enhancer13, 14, 16 alleviates concerns about the effect of BCL11a inactivation in non-erythroid cells because BCL11A deficiency in murine models has been associated with impaired B lymphocyte and hematopoietic stem cell (HSC) development17, 18 or about influencing aspects of erythroid differentiation/maturation raised by targeting other transcription factors involved in silencing (i.e KLF1 and ZBTB7A). Finally, it is known that patients with BCL11A haploinsufficiency have increased levels of HbF at levels likely to be therapeutic for patients with β-globin disorders 19, 20.…”
Section: Introductionmentioning
confidence: 99%
“…Its roles in erythropoiesis besides HbF silencing are modest. However BCL11A plays essential roles in various hematopoietic lineages, including in B-lymphocytes, dendritic cells and hematopoietic stem cells 18,[23][24][25] . In addition, it has functions beyond hematopoiesis not only in the central nervous system but also in breast and pancreatic cells 26,27 .…”
Section: Discussionmentioning
confidence: 99%